Association between salivary and serum Interleukin-39 and osteopontin in periodontitis patients: case-control study - Al Lami, Sarah J; AL-Drobie , Ban; Salami, Anas (Journal of Baghdad College of Dentistry, 2025)
Background: Cytokines have a crucial role in developing chronic inflammation and the inflammatory response. Some interleukins, such as interleukin-39 (IL-39), have unknown specific roles in the pathogenesis of periodontitis. Osteopontin has been shown to be a multifunctional cytokine and a unique modulator of innate and adaptive immune responses. Therefore, the study's objective was to measure IL-39 and osteopontin level and their ratio in the saliva and serum of periodontitis patients in Iraq. Materials and methods: This case-control study include 78 individuals with an age range of 25-60 years (40 periodontitis patients without clinical intervention and 38 healthy volunteers). Levels of salivary, serum IL-39 and osteopontin were determined for both groups, utilizing the Enzyme-Linked Immunosorbent Assay technique. The Social Science Statistical Package (Version 26; SPSS, IBM) was utilized for statistical analysis. Results: Serum levels of IL-39 and osteopontin were significantly elevated in periodontitis patients compared to healthy participants (p < 0.001 and p = 0.001, respectively). A similar pattern was observed in saliva, with significantly higher levels of IL-39 and OPN in periodontitis patients. Positive correlations were detected between serum and salivary levels of IL-39 (p = 0.037) and OPN (p = 0.003). Diagnostic validity tests demonstrated that IL-39 and OPN assays exhibited high sensitivity and negative predictive value (100%), and high accuracy (94.87% to 100%). The area under the curve values approached 1.0. Conclusion: Elevated saliva interleukin-39 and Osteopontin levels and elevated serum parameters are strongly associated with periodontitis.